Bat community in a cave from eastern Brazil, including a new record of Lionycteris (Phyllostomidae, Glossophaginae) - Trajano, Eleonora; Gimenez, Eliana A. [UNESP] (Taylor & Francis, 1998)
A cave bat community from a semiarid region in eastern Brazil was studied during the dry season. A high diversity was observed, with thirteen species recorded. Except for Micronycteris minuta and Lionycteris spurrelli, these bats were also found in other Brazilian karstic areas. The commonest species were the hematophague Desmodus rotundus, the omnivore Carollia perspicillata, and the insectivore Natalus stramineus. The bats formed itinerant colonies, moving frequently inside the cave. L. spurrelli was previously known from Amazonia, usually associated with evergreen forests. The present record extends its range 1600 km to the south. A disjunct distribution explains some morphological differentiation between Amazonia and Olhos d'Agua cave populations. The latter may be a relict of former continuous forest vegetation, which has been fragmented after the climatic optimum. Dispersion through the Cerrado forest gallery is also possible.
Keywords: Bat ecology; Brazil; Cave bats; Lionycteris spurrelli; Minas Gerais; Range extension; Carollia perspicillata; Lionycteris; Natalus stramineus